APPLICATION OF A MATHEMATICAL MODEL OF GAUSS ATMOSPHERIC DISPERSION OF SULPHUR DIOXIDE - Taipe H., Eduardo (2003)
The Gaussian dispersion model PTC is applied to simulate the atmospheric dispersion of S02 produced by a chimney of 20 m height and 0.7 m in diameter at the Thermal Power Tintaya (Cusco) continuously ejected environmental S02 261 461 mg / sa 17.2 m / s. The model evaluates the distance of maximum concentration at ground level to 750 m from the source and the average concentration of 3.06 mg place S02/m3